Estrat??gia de patroc??nio: uma perspectiva pautada na qualidade do evento, satisfa????o do espectador e sua experi??ncia com a marca patrocinadora - Yamamoto, Paula Yumi (2016)
The decision to sponsor an event involves the expectation of exchange gains, among which the increase of sponsor???s brand equity. Considering the current scenario, as Brazil is hosting some of the most viewed sporting events in the world, the importance of the sports to connect brand and consumer increases by providing a meeting in an environment surrounded by unique and memorable moments. In an attempt to understand how the value of a brand is influenced by a sport sponsorship decision, this paper suggests the impact of three factors: brand experience, sport event quality and spectator satisfaction. Thus, the study conducts to a reflection about the sports environment elements that can be molded in order to provide better return to sponsor investment, while it helps sports managers to convince new sponsors. The basis of this research is structured on the assumption that the sport event quality influences sponsor???s brand equity, and introduces the spectators??? experience with the sponsoring brand and their satisfaction with the event as mediators variables. This is a quantitative research based on structured questionnaire answered by beach volleyball spectators on the 8th Circuito Brasileiro Banco do Brasil de V??lei de Praia. For data analysis, it is used the technique of structural equation modeling. As a result, it is confirmed that the quality of the event influences the sponsors??? brand equity and that the main points of management are the peripheral elements, such as seat comfort, crowd experience, facility access, game atmosphere, frontline employees, etc. The main elements such as player performance and the final score are beyond managers??? control. In conclusion, a high-quality event generates higher levels of satisfaction, which confirms increases in sponsors??? brand equity. In addition, the spectators??? experience with the sponsoring brand also confirms the positive impact on sponsors??? brand equity. Thus, a sports sponsor should interact with the spectators, exploring strategies and actions for each of brand experience dimensions (sensory, affective, intellectual, behavioral and relational). The quality of the event, the spectators??? satisfaction with the event and their sponsor's brand experience are elements that, if well managed and explored, contribute positively to sponsors??? brand equity. These strategies should be aimed both by sports managers, as a way to attract and retain sponsors, and by sponsors??? brand managers, as a way to get return on investment. For this purpose, the sporting managers and sponsors should undertake a planning together to offer a high-quality event enabling an environment that provides spectators??? satisfaction and a positive experience with the sponsor brand.